Ideal cardiovascular health, inflammation, and arterial stiffness in the transition to adulthood. (15th May 2022) - Oliveira, Ricardo Santos; Wehrmeister, Fernando C.; Oliveira, Isabel O.; Gonçalves, Helen; Menezes, Ana Maria Baptista
Abstract: Background: Ideal cardiovascular health (ICH) promotes primordial prevention of cardiovascular diseases. However, whether ICH is associated with arterial stiffness in the transition to adulthood and the mechanisms associated have yet to be shown. The aims of this investigation were to: 1) investigate whether there is a prospective association between ICH and pulse wave velocity (PWV) in the transition to adulthood; and 2) to stablish whether the association between ICH and PWV is mediated by inflammatory markers. Methods: Participants were part of the 1993 Pelotas Birth Cohort and follow-ups at 18- and 22-years were used in this study. At the age of 18 years, ICH was computed as the presence of ideal for the following metrics: physical activity, diet, smoking, blood cholesterol and glucose, blood pressure, and body mass index. At the age of 22 years, aortic PWV was obtained as well as interleukin-6 (IL-6) and C-reactive protein (CRP). Results: A total of 3528 (1851 females) were included in the analysis. A significant linear effect was observed for ICH on PWV. After adjusting for socioeconomical status, skin colour, birth weight, and mother schooling male and female participants with better ICH profile had PWV of 0.70 m·s −1 and 0.60 m·s − slower than participants with poor ICH. No evidence for a mediating role of inflammatory markers was observed for male (<1%) and female (<5%). Conclusions: ICH is inversely associated with PWV among male and female in the transition to adulthood with no mediating role of inflammation. Highlights: Adolescents' cardiovascular health is associated with early adulthood arterial stiffness. Inflammation had no influence on the association between cardiovascular risk and arterial stiffness. Atherosclerosis start during childhood and primordial prevention is key.